PENGARUH PENYULUHAN DENGAN METODE DISKUSI KELOMPOK TERHADAP PENGETAHUAN TENTANG TEKHNIK PENYIMPANAN ASI IBU BEKERJA - Rotua Lenawati Tindaon; Parida Hanum (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
The low coverage of exclusive breastfeeding shows that not many mothers have succeeded in giving exclusive breastfeeding because the majority of working mothers. Work is not an obstacle for a mother to give milk to the baby. Therefore, working mothers need to be taught how to express milk, how to give milk and how to store breast milk. Health education is organized to increase the knowledge, awareness, willingness, and ability of working mothers to keep breastfeeding babies. Knowledge of breast milk storage techniques will support the success of exclusive breastfeeding for optimal child growth and development. Solution In accordance with the problem In order for the working mother to continue to give ASI, namely Lactation Management through health education, is held to increase the knowledge, awareness, willingness, and ability of the working mother to continue breastfeeding the baby. The long-term goal to be achieved in research is to identify and analyze the Effects of Counseling with Group Discussion Methods on Knowledge of Breast Milk Storage Techniques in Working Mothers. Specific targets to be achieved so that every health worker working in a health facility applies Counseling to working mothers about breastfeeding storage techniques so that exclusive breastfeeding can be achieved. Stages of Research Methods to be conducted using the Quasy Experiment design, with the target of working mothers who have babies 0-24 month given Counseling. Data collection methods with questionnaires and interviews. Data analysis method uses dependent t-test. Where in the paired groups, the same subjects were examined before and after the intervention (designs before and after). The results of the study through the Knowledge Questionnaire about ASI Storage Technique obtained P-value 0,000. It can be concluded that there is an effect of counseling with the Group Discussion Method on the ASI Storage Technique in Working Mothers.